(3QSGdI aj bhGfjf GdefWbs
(3ChdgG (B:s
(3GdMeO ddg CeG HYO agPg QSGdI ai GdefWb WdHgG ef HYV GdENhGf aUd GddaX EeG OGd s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg (B: (3hCeG GdbjGS GdCSJKfGFi agi CeG eJUdI ChI efaUdI aEf cGfJ eJUdI aGSJKfGA Yjf GdebOe s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs